THE IMPACT OF FUNCTIONAL DISORDERS ON THE STRUCTURE OF THE PROXIMAL PART OF THE THIGH AND THE HIP JOINT IN PATIENTS WITH A HISTORY OF STROKE - Smyrnova, O. L.; Shkurupii, O. I. (Rehabilitation and Recreation, 2022)
The aim. To establish the impact of functional impairment in patients with the stroke on the structure of the proximal part of the thigh and dysfunction of the hip joint. Material. The criteria for the inclusion of patients were cases of stroke with hemiplegia in the anamnesis. 87 patients participated in the study, who were divided into 4 groups: group 1 included 25 patients with signs of osteoarthritis (OA) of the hip, group 2 – 20 patients with signs of decreased mineral density of the proximal femur (PM), 3 – 12 patients with signs of OA and decreased mineral density of PM, 4 – 30 patients without signs of OA and decreased mineral density of PM. All patients underwent questionnaires, anthropometry, research of muscle strength of the lower limbs, range of motion in the hip, motor functions of the lower limbs, static and dynamic balance and risk of falling, level of spasticity, cardiorespiratory endurance, walking speed, level of cognitive functions were assessed. The results. Mineral density in PM in groups 2 and 3 was lower compared to representatives of group 4. Mineral density in group 1 was the highest and was 1244.2±51.6 HU (р<0.05). The lowest muscle strength was in group 3. Analysis of the range of motion in the hip showed that the greatest limitations were in groups 1 and 3. The lowest stage of motor recovery according to CMSA was recorded in the 3rd observation group. The value of motor functions according to CMSA in group 2 was greater than that of group 3, but lower than that of groups 1 and 4. The greatest disturbance of static balance was recorded in group 2, and the lowest level of dynamic balance was recorded in group 3. The value of the TUG test indicated the presence of reduced mobility and increased risk of falling in representatives of groups 2 and 3. In these groups, there was a decrease in walking speed and general endurance. Conclusions. It was found that in patients with the consequences of stroke and coxarthrosis, despite the decrease in the volume of movements in the hip, the density of PM, the speed and length of walking, and general mobility were increased. The most pronounced movement disorders were in the group of patients who combined signs of arthrosis and a decrease in bone mineral density, which was manifested by a violation of the muscle strength of the lower limb, limitation of movements in the hip, limitations of mobility, a decrease in walking speed and general endurance.